Uji Akurasi Arah Kiblat Menggunakan Fitur Kompas Kiblat Pada Aplikasi Quran Kemenag Versi 2.1.4 - Santi Okta Sriani; Laiyina Ukhti (Islamic Astronomy Department, Sharia and Law Faculty, 2022)
Quran Kemenag is an Android-based application or software that is easy to download on the Google PlayStore which has one interesting feature, namely the Qibla compass. The Qibla compass feature is interesting because it utilizes the device's compass sensor that users can immediately find out the Qibla direction indicated by the feature and according to the circumstances of the surrounding environment, starting with calibration first. With the Qibla compass feature in the Quran Kemenag application, it can make it easier for people to determine the Qibla direction and can use it whenever and wherever they are. The purpose of this study is to explain in more detail the method of measuring the Qibla direction using Qibla compass on Quran kemenag application and to explain in detail the accuracy of the Qibla direction using the Qibla compass on Quran Kemenag application. The research method is included in the type of qualitative research that is descriptive (descriptive research) and classified as field research (Field Research), namely direct observation of objects studied in the field. The primary data sources for this research are observation data and measurement results data from features in the Quran Kemenag application Version 2.1.4. The secondary data is reports of collaborative community service activities for lecturers and students. This research found the results that Qibla compass on Quran Kemenag application is very easy to use, namely by opening the application then clicking the compass feature and placing the cellphone on a calibrated flat plane, the feature shows the Qibla direction. The level of accuracy of the Qibla direction from the compass feature is different from the theodolite results, namely by a difference of 1'-2'. So that the differences make the Qibla compass feature on Quran Kemenag application is not suitable to be used as the main reference in determining the Qibla direction, for example for the construction of mosques and meunasah. But this application can be used in an emergency.